2004
DOI: 10.1021/cm0345669
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Tribological Studies of Stearic Acid Self-Assembled Monolayers on Polymer-Coated Silicon Surface

Abstract: We present a good alternative method to improve the tribological properties of polymer films by chemisorbing a long-chain monolayer on the functional polymer surface. Thus, a novel self-assembled monolayer is successfully prepared on a silicon substrate coated with amino-group-containing polyethyleneimine (PEI) by the chemical adsorption of stearic acid (STA) molecules. The formation and structure of the STA-PEI film are characterized by means of contact-angle measurement and ellipsometric thickness measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…1,2) Until now, (3-Aminopropyl)-triethoxysilane (APTES), 1) polyethyleneimine (PEI), 13) polyethyleneglycol (PEG) 4) and polyethylene (PE). 1,4) have been proposed as a surface linker material for the sensing or recognition of biological elements in biosensors. Among these materials, PEI has been considered as a viable surface linker owing to its simple controllability and biofunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Until now, (3-Aminopropyl)-triethoxysilane (APTES), 1) polyethyleneimine (PEI), 13) polyethyleneglycol (PEG) 4) and polyethylene (PE). 1,4) have been proposed as a surface linker material for the sensing or recognition of biological elements in biosensors. Among these materials, PEI has been considered as a viable surface linker owing to its simple controllability and biofunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…The water contact angle for the PEImodified surface is 8°, characteristic of PEI monolayer covered surface [29]. After anionic PSS adsorption on the PEI surface, the contact angle increases to 36°.…”
Section: Resultsmentioning
confidence: 98%
“…A promising way to further ameliorate the tribological behaviors of SAMs, especially the load-carrying capacity, is to enhance the stability of the films. It is revealed that the SAMFs with synergetic components generally exhibits longer anti-wear life (Ren et al, 2003;Ren et al, 2004;a, Song et al, 2008). The reason for the enhanced wear resistance is ascribed to the special structures of the SAMFs.…”
Section: Functional Group Embedded Samfsmentioning
confidence: 99%